The Self-Awareness Multilevel Assessment Scale, a New Tool for the Assessment of Self-Awareness After Severe Acquired Brain Injury: Preliminary Findings - Bivona, Umberto; Ciurli, Paola; Ferri, Giulia; Fontanelli, Tiziana; Lucatello, Susanna; Donvito, Teresa; Villalobos, Dolores; Cellupica, Laura; Mungiello, Fabiana; Lo Sterzo, Paola; Ferraro, Amalia; Giandotti, Eleonora; et al. (Frontiers in Psychology, 2020)
Self-awareness (SA) is frequently impaired after severe acquired brain injury (sABI) and may lead to reduced subject’s compliance to treatment, worse functional outcome and high caregiver distress. Considering multifaceted nature of SA, a specific and effective assessment is crucial to address treatment of impairment SA (ISA). Many tools can currently assess ISA; however, they have some important limits. In the present study we proposed the Self-Awareness Multilevel Assessment Scale (SAMAS), a new scale for assessment of SA at different levels (i.e., declarative, emergent and anticipatory) across all domains of functioning. The SAMAS has been designed to be administered by the cognitive/behavioural therapist with the involvement of a patients’ relative. Finding showed that the SAMAS allowed specifically assessing SA at a declarative level and on all possible functional domains. More interestingly, it seems also able to assess both emergent and anticipatory SA, thus overcoming some important limits of other current assessment methods. Our finding are consistent with a holistic perspective of the patient with sABI, since thanks to the combined use of assessing tools, the SAMAS can provide an accurate diagnosis of ISA, thus better addressing the neurorehabilitation treatment and, accordingly, reducing the possible occurrence of its primary and secondary implications.